2016
DOI: 10.1111/anae.13623
|View full text |Cite
|
Sign up to set email alerts
|

Estimated costs before, during and after the introduction of the emergency laparotomy pathway quality improvement care (ELPQuIC) bundle

Abstract: Implementation of a quality improvement bundle for peri-operative management of emergency laparotomy (ELPQuIC) improved mortality in a previous study. We used data from one site that participated in that study to examine whether it was associated with the cost of care. We collected data from 396 patients: 144 before, 144 during and 108 after implementation of the bundle. We estimated costs incurred using previously published methodology based on the time the patient spent in hospital, in the operating theatre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…Emergency laparotomy is a commonly performed surgical procedure, with a high 30-day mortality [ 8 – 11 ] and wide variations in the standards of care delivered [ 10 12 ]. Previous small studies of quality improvement in this area have improved care delivery and reduced mortality without increasing costs [ 10 , 13 , 14 ]. The EPOCH trial was designed to establish whether a quality improvement approach could reduce mortality and length of hospital stay for this patient group, when delivered at a national level.…”
Section: Introductionmentioning
confidence: 99%
“…Emergency laparotomy is a commonly performed surgical procedure, with a high 30-day mortality [ 8 – 11 ] and wide variations in the standards of care delivered [ 10 12 ]. Previous small studies of quality improvement in this area have improved care delivery and reduced mortality without increasing costs [ 10 , 13 , 14 ]. The EPOCH trial was designed to establish whether a quality improvement approach could reduce mortality and length of hospital stay for this patient group, when delivered at a national level.…”
Section: Introductionmentioning
confidence: 99%
“…It guides the junior doctor to early identification of abnormal physiology (sepsis, SIRS, high MEWS or high P‐POSSUM) and provides a checklist of jobs to do to initiate resuscitation (fluids, antibiotics, analgesia) while triggering early involvement of other practitioners, investigation and acceleration of definitive treatment. We wholeheartedly agree that early involvement of senior clinicians and routine use of critical care for postoperative management of these patients is important and have both reported the benefits of both these elsewhere and been involved in producing such guidance . Locally, we aspire to have consultant surgeon, anaesthetist and intensivist involvement in all patients undergoing emergency laparotomy, not only those with a P‐POSSUM mortality risk > 5% or > 10%.…”
mentioning
confidence: 75%
“…Earlier, smaller studies have shown that marked improvement may take time and can continue after the intervention period. 59 There are other plausible explanations for our failure to change the primary outcome metrics. It is possible that our programme theory was incorrect, and there was only a weak causal link between the interventions and ultimate outcomes.…”
Section: Discussionmentioning
confidence: 99%